(untitled) (Oxford, 2007)
Lumb & Jones' is the definitive reference in veterinary anesthesia and analgesia, covering all large and small animal species and a full array of clinical conditions and diseases. This new edition is greatly expanded and revised – an essential and comprehensive text for anyone with a special interest in animal anesthesia and analgesia.
Keywords: Veterinary anesthesia,Analgesia,Chứng mất cảm giác đau ở thú